The Influence of Preeclampsia, Advanced Maternal Age and Maternal Obesity in Neonatal Outcomes Among Women with Gestational Diabetes - Nunes, Joana Sousa; Ladeiras, Rita; Machado, Luísa; Coelho, Diana; Duarte, Carla; Furtado, José Manuel (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective The present study aims to analyze adverse fetal or neonatal outcomes in women with gestational diabetes, including fetal death, preterm deliveries, birthweight, neonatal morbidity and mortality, as well as the synergic effect of concomitant pregnancy risk factors and poor obstetric outcomes, as advanced maternal age, maternal obesity and pre-eclampsia in their worsening.Methods The present cohort retrospective study included all pregnant women with gestational diabetes, with surveillance and childbirth at the Hospital da Senhora da Oliveira during the years of 2017 and 2018. The data were collected from the medical electronic records registered in health informatic programs Sclinico and Obscare, and statistical simple and multivariate analysis was done using IBM SPSS Statistics.Results The study participants included 301 pregnant women that contributed to 7.36% of the total institution childbirths of the same years, in a total of 300 live births. It was analyzed the influence of pre-eclampsia coexistence in neonatal morbidity (p = 0.004), in the occurrence of newborns of low and very low birthweight (p < 0.01) and in preterm deliveries (p < 0.01). The influence of maternal obesity (p = 0.270; p = 0.992; p = 0.684) and of advanced maternal age in these 3 outcomes was also analyzed (p = 0,806; p = 0.879; p = 0.985).Using a multivariate analysis, the only models with statistic significance to predict the three neonatal outcomes included only pre-eclampsia (p = 0.04; p < 0.01; p < 0.01).Conclusion Only coexistence of pre-eclampsia showed an association with adverse neonatal outcomes (neonatal morbidity, newborns of low and very low birthweight and preterm deliveries) and can be used as a predictor of them in women with gestational diabetes.
Keywords: gestational diabetes; advanced maternal age; maternal obesity; preeclampsia; neonatal outcomes